PENGARUH PENGAWASAN DINAS LLAJ TERHADAP KEDISIPLINAN PENGEMUDI ANGKUTAN UMUM DI KOTA BOGOR - Muharam Firdaus; Denny Hernawan; Ginung Pratidina (Jurnal Governansi, 2016)
The purpose of this study is to determine the effect of Discipline Supervision by the Agency (DLLAJ) towards public transportation driver in the city of Bogor, so  discipline of public transportation drivers in the city of Bogor can be achieved.                 Research method used in this study is associative correlation. The data used are primary and secondary data. Primary data are collected by distributing a questionnaire, and supported by the observations and interviews. Collection of secondary data sourced from documents, literature and related researchs. Research sample are 93 drivers from nine routes of public transportation that crosses main route (Padjajaran Road) and 55 officers of DLLAJ agency Bogor City.                 Based on the discussion can be concluded that the effect of supervision taken by Dinas LLAJ towards public transportation in the city of Bogor basically been implemented quite well. Based on the conclusion, the author recommend : DLLAJ officers must provide supervision continuosly, improve traffic infrastructure, especially at the point of congestion and hustle to immediately known root causes. For example, due to lack of traffic signs or in the absence of road markings (zebra crossing) so as to create traffic conditions that are safe, comfortable and smooth. Keywords: Supervision, Discipline, Public Transportation